New contributions to the native and alien flora in riparian habitats of the Cantabrian watershed (Northern Spain) - Liendo, Diego; Campos, Juan Antonio; Biurrun, Idoia; García-Mijangos, Itziar (Lazaroa, 2016)
As a result of a floristic survey carried out in riparian habitats of northern Spain, new chorological data are provided for 9 alien and 6 native plant species. Some species are reported for the first time at regional scale, such as Carex strigosa, Helianthus x laetiflorus and Persicaria pensylvanica in Cantabria. Also noteworthy is the finding of naturalised populations of the North American grass Muhlenbergia schreberi at the Urumea river basin, which represents the second reference for the Iberian Peninsula.